Operações abusivas na banca eletrónica - Alves, Inês Custódio (2019)
The dissemination of new information and communication technologies has increased the practice of "new crimes": computer crimes. The typology of attacks on cyberspace is varied, however, in the present study, we look in more detail about the cyber attacks perpetrated in the services of homebanking. Phishing and pharming appear as the most recurring computer fraud techniques, which are not always easy to predict and combat, due to hackers anonymity. Such fraudulent schemes result in losses that will be allocated in accordance with the conduct of the parties in the user agreement. Within a complex negotiating relationship, the fair distribution of the damages obtained will be done in function of the fulfillment of duties or lack thereof. Thus, in light of the new Legal Regime of Payment and Electronic Currency Services, the parties' duties in the contractual relationship are the touchstone in the allocation of such damages. The present study is used to determine who will be responsible for damages caused by improper use of the homebanking system. Currently, changes in the area of payment systems have been in the spotlight due to the new Payment Systems Directive, Directive 2015/2366 of the European Parliament and of the Council of 25 November on payment services in the European Union internal market, which focuses on the security of both institutions and consumers and on user data protection.